2015
DOI: 10.1136/archdischild-2014-307478
|View full text |Cite
|
Sign up to set email alerts
|

Normal saline flushes performed once daily maintain peripheral intravenous catheter patency: a randomised controlled trial

Abstract: The study is registered in the international database ClinicalTrial.gov under registration number NCT02221024.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 10 publications
1
22
0
Order By: Relevance
“…Schreiber et al studied 400 children and found no significant difference in PIVC failure between different flushing frequencies (12 vs. 24 h). Differences between that study and our study were that flushes in Schreiber et al ' study were delivered using prefilled syringes (ours were manual), and apart from flushes, their patients did not receive intravenous therapy following enrolment .…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…Schreiber et al studied 400 children and found no significant difference in PIVC failure between different flushing frequencies (12 vs. 24 h). Differences between that study and our study were that flushes in Schreiber et al ' study were delivered using prefilled syringes (ours were manual), and apart from flushes, their patients did not receive intravenous therapy following enrolment .…”
Section: Discussionmentioning
confidence: 98%
“…Schreiber et al studied 400 children and found no significant difference in PIVC failure between different flushing frequencies (12 vs. 24 h). Differences between that study and our study were that flushes in Schreiber et al ' study were delivered using prefilled syringes (ours were manual), and apart from flushes, their patients did not receive intravenous therapy following enrolment . The results of our study contextualise the use of intermittent flushing in the paediatric clinical setting where medications other than normotonic sodium chloride are infused with the potential to provide various degrees of venous irritation, depending on the chemical make up of the medication that could contribute to PIVC failure.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations